Profiles of free fatty acids, free amino acids, and volatile compounds of milk bases fermented by Lactobacillus casei GBHM-21 with different fat levels. Issue 1 (2nd January 2016) - Bao, Zhining; Xiong, Jian; Lin, Weifeng; Ye, Jun
Abstract : Milk fat content is an important factor affecting the flavor of fermented dairy products. The effects of milk fat concentration (0–90) g·L −1 on the changes of flavor-related compounds in the milk base fermented by Lactobacillus casei GBHM-21 were investigated. The amount of some of the free fatty acids (FFAs) and free amino acids (FFAs) increased as the fat concentration increased, accompanied by a concomitant increase of the quantities and intensities of volatile compounds (VCs). A substantial increase in long-chain fatty acids was observed, whereas no significant effect on short-chain fatty acids was observed. The amount of the total FFA was linearly and positively correlated with the total FAA. The most abundant group of VCs was ketones for low-fat samples and carbonyl acids for high-fat samples. The level of FFA-derived ketones increased dramatically first and then reached a plateau, while FFA-derived carbonyl acids continuously increased. These results provided valuable informative utilization of milk fat in the fermented industry.